A review on utilisation of biomass from rice industry as a source of renewable energy - Jeng, Shiun Lim (2012)
Volatile oil price and growing emphasis on environmental conservation have stimulated the development and utilisation of biomass as a vital source of renewable energy. In reducing the global dependency on fossil fuels, rice husk and rice straw which are the widely abundant agricultural wastes from the rice industry have a vital role to play. This paper reviews the key aspects of the utilisation of rice husk and rice straw as important sources of renewable energy. The paper provides some essential background information that includes the physical and chemical characteristics that dictates the quality of these rice biomasses. This paper also describes the various chemical and physical pretreatment techniques that can facilitate handling and transportation of rice straw and husk. Finally, the paper presents the state-of-the-art on thermo-chemical and bio-chemical technologies to convert rice husk and rice straw into energy.